Current extraction techniques towards bioactive compounds from brewers spent grain A review - Lopes, Maria Teresa (2020)
Background: Brewers spent grain is one of the most abundant by-products of the brewing industry and is rich in various bioactive compounds (phenolic acids, insoluble dietary fiber and proteins). While at the present brewers spent grain is mainly used as animal feed its rich nutritional content makes it an interesting alternative for food applications. Scope and approach: As the range of applications of the bioactive compounds extracted from by-products has been growing in recent years, there is the need to obtain and characterize these bioactive compounds. Extraction methods (supercritical carbon dioxide, autohydrolysis, alkaline hydrolysis, solvent extraction, ultrasound assisted extraction, dilute acid hydrolysis, enzymatic hydrolysis, microwave assisted extraction) have been developed and are always being subjected to new approaches to allow better extraction yields of the bioactive compounds. Key findings and conclusions: This review aims to provide a better understanding of the current advantages and limitations of brewers spent grain extraction processes and to provide a background of brewers spent grain composition and applications.